The Activity of Calcium Glycerophosphate and Fluoride against Cariogenic Biofilms of Streptococcus mutans and Candida albicans Formed In Vitro - Thamires Priscila Cavazana; Thayse Yumi Hosida; Caio Sampaio; Leonardo Antônio de Morais; Douglas Roberto Monteiro; Juliano Pelim Pessan; Alberto Carlos Botazzo Delbem (MDPI AG, 2023)
This study evaluated the effects of calcium glycerophosphate (CaGP), with or without fluoride (F), on dual-species biofilms of Streptococcus mutans and Candida albicans. The biofilms were treated three times with 0.125, 0.25, and 0.5% CaGP solutions, with or without 500 ppm F (NaF). Additionally, 500 and 1100 ppm F-solutions and artificial saliva served as controls. After the final treatment, the microbial viability and biofilm structure, metabolic activity, total biomass production, and the composition of the extracellular matrix composition were analyzed. Regardless of the presence of F, 0.25 and 0.5% CaGP promoted a higher biomass production and metabolic activity increase than the controls (p < 0.05). F-free CaGP solutions reduced bacterial cell population significantly more than the 500 ppm F group or the negative control (p < 0.05). All the groups reduced the proteins, and 0.5% CaGP combined with F led to the highest reduction in the carbohydrate and nucleic acids content of the extracellular matrix (p < 0.05). It can be concluded that CaGP alone affected the number of bacterial cells and, when combined with F, reduced its production of biomass, metabolic activity, and the expression of the extracellular matrix components.